2022
DOI: 10.5194/acp-22-2049-2022
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of CH<sub>2</sub>Cl<sub>2</sub> and CHCl<sub>3</sub> show efficient transport pathways for very short-lived species into the lower stratosphere via the Asian and the North American summer monsoon

Abstract: Abstract. Efficient transport pathways for ozone-depleting very short-lived substances (VSLSs) from their source regions into the stratosphere are a matter of current scientific debate; however they have yet to be fully identified on an observational basis. Understanding the increasing impact of chlorine-containing VSLSs (Cl-VSLSs) on stratospheric ozone depletion is important in order to validate and improve model simulations and future predictions. We report on a transport study using airborne in situ measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…Tropospheric θ ranges define maximal vertical extensions where new transport modes in CLaMS 2.0 are evaluated in terms of the root mean square differences between observations and model results. The instruments and their performance during StratoClim are described in von Hobe et al (2021) and during WISE in Krasauskas et al (2021) and Lauther et al (2022). First, the upward propagation of the CO 2 seasonal cycle during StratoClim is better reproduced in the CLaMS 2.0 version including parameterization of unresolved convective updrafts and improved boundary conditions (I1C1T0-EI/E5) compared to the former model version CLaMS 1.0 (C-1.0-EI/E5) and even better than by the CarbonTracker data set as can be deduced from the comparison around θ = 380 K.…”
Section: N 2 O Co 2 and O 3 Profilesmentioning
confidence: 99%
“…Tropospheric θ ranges define maximal vertical extensions where new transport modes in CLaMS 2.0 are evaluated in terms of the root mean square differences between observations and model results. The instruments and their performance during StratoClim are described in von Hobe et al (2021) and during WISE in Krasauskas et al (2021) and Lauther et al (2022). First, the upward propagation of the CO 2 seasonal cycle during StratoClim is better reproduced in the CLaMS 2.0 version including parameterization of unresolved convective updrafts and improved boundary conditions (I1C1T0-EI/E5) compared to the former model version CLaMS 1.0 (C-1.0-EI/E5) and even better than by the CarbonTracker data set as can be deduced from the comparison around θ = 380 K.…”
Section: N 2 O Co 2 and O 3 Profilesmentioning
confidence: 99%
“…The western Pacific mode of the ASMA dominated by eastward shedding is strongly impacted by the background mid‐latitude dynamics such as the subtropical jet (Rupp & Haynes, 2021). Aerosol and other tracer gases within the ASMA will be partially transported to the lower northern extra‐tropical stratosphere via the western Pacific mode of the ASMA (Fujiwara et al, 2021; Lauther et al, 2022; Vogel et al, 2016; Wetzel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The midlatitude and tropical origin of the tropospheric air agrees with complementary work on other trace gases along the same flight track but at lower flight altitudes. Lauther et al (2021) linked in situ observed, exceptionally low concentrations of chlorine containing very short-lived substances to fast vertical transport in TC Maria from weak emission source regions in the tropical Atlantic PBL. Rotermund et al (2021) found increased concentrations of bromine, which they connected to lifting by TCs and convection.…”
Section: Discussionmentioning
confidence: 94%